The Dining in the Dark Phenomenon - Siegfried Saerberg (Disability Studies Quarterly, 2007)
In the last fourteen years in Europe, a phenomenon has developed that I call "Dining in the Dark." Its primary success has been to promote communication between blind and sighted people -- through a mediation process (rather than any simulation of blindness) -- and to show how a disabling society constructs blindness-related problems. Second, it demonstrates real possibilities available to blind people and to the ways a more enabling society could accommodate their needs and skills. Third, the phenomenon has enhanced self-confidence among blind and visually disabled food-service workers. But such "demonstrations" raise questions about how best to design and structure future events, and whether "Dining in the Dark" as for-profit businesses are also successful at mediating blindness. I also consider whether "Dining in the Dark" events function as modern-day, acceptable "freak shows." Finally, I suggest how the concept of liminality can help us better understand and interpret these phenomenon and their achievements.
Keywords: Dining in the Dark; Blindness; Mediation; Freak Show; Liminality